SISTEM SYARAF MANUSIA DALAM TUTORIAL CBI: USAHA MENINGKATKAN KETERAMPILAN GENERIK SAINS - Asep Mulyani (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2012)
The aim of this research to know the effect of tutorial CBI toward generic science skills in human nervous system concept. One of senior high school at Garut regency, West Jawa was selected as the location of study. The subject of this research consisted of 153 students. 77 students as experimental class treated by using the tutorial CBI and 76 students as control class treated by using the conventional approach. Each group was gifted pretest ang posttest on generic science skills of human nervous system concept. The obtained data were then submitted to statistical analyses such as Mann-Whytney U Test. The finding revealed that there was significant effect of the tutorial CBI on student’s generic science skills of human nervous system concept. Furthermore, the experimental class obtained higher N-gain than the control class. The average of generic sciences skills N-Gain in experimental class was 0.65 and control class was 0.43. The findings suggested that learning human nervous system concept by using the tutorial CBI was effectifully. Finally, the study suggested that the tutorial CBI can be used as alternative approach in teaching biology especially to enhance generic science skills in human nervous system concept.